HUBUNGAN POWER OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK SISWA PUTRA KELAS X SMAN 12 PEKANBARU - Winarta, Roby; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: The problem in this study is based on observations by the author of the male students of grade X SMAN 12 Pekanbaru seen that there are still many students who obtain low yields in the sport long jump is caused by muscle power leg students who have not maximized so that repulsion leg students when resting does not produce a strong boost in the jump. Apart from the power of leg muscle, leg muscle strength factor of students still can not be said to be good, less good leg muscle strength possessed by students resulted in the lack of good results students leap. Then the running speed in doing the long jump also still looks less than the maximum and that the impact on the outcome of a leap to short. Then some students still looks stiff in terms of flexibility of the body is less maximum. Until lead to less favorable long jump results of the students, then in the long jump sports facilities and infrastructure still can not be said to be good because it looks sand still lacking a lot and it makes students not perfect landing , The purpose of this study was to determine the relationship of limb muscle power with the result of long jump squat style male student grade X SMAN 12 Pekanbaru. This type of research is correlational, Correlational is a statistical tool, which can be used to compare the results of measurements of two different variables. The population in this study were all male students of grade X SMAN 12 Pekanbaru totaling 177 people. The sampling techniques, using proportionate stratified random sampling technique. Thus, in this study the number of samples to be studied were 20 male students of grade X SMAN 12 Pekanbaru. Results of analysis showed that rhitung = 0.514 and the significance level of 5% was found rtabel = 0.444 with a strong relationship level category.Key Words: Power legs muscles, squat-style long jump results